Mixed-mode fracture model to quantify local toughness in nacre-like alumina. Issue 10 (August 2023) - Vilchez, Victoria; Pelissari, Pedro I.B.G.B.; Pandolfelli, Victor C.; Bouville, Florian
Abstract: With the progress of ceramic engineering, tough technical ceramics such as nacre-like alumina now exhibit complex fracture patterns with high degrees of deflection, branching and bridging. If these mechanisms highly contribute to improving crack resistance, the crack geometries go beyond the hypotheses assumed in standard techniques to quantify toughness, making it difficult to understand the mechanisms responsible for crack propagation. We report a robust local solution based on a combination of analytical formulas and finite element analysis to accurately estimate the effective stress intensity factors at the tips of multiple deflected cracks. The influence of sample size on local R-curves is analysed and shown to be less important relative to standard methods. We use this method to evaluate the direct influence of zirconia nanoparticles in the nacre-like structure and highlight the role of these findings in the understanding of mechanical response and future optimisation of highly textured tough ceramics.